Trickle-Down Holocaust: Racism in the North American Context - Terrell, Joanne Marie ca. 20./21. Jh. (Concilium, 2023)
Racism is a world-defining by-product of Western European nations' agrarian capitalism, articulated as religious, philosophical, and scientistic justification for the genocide of peoples of color and appropriation of their natural resources during the era of exploration, empire, and Enlightenment. With the wholesale enslavement of African peoples as chattel, rampant sexual exploitation of African women was a tool of empire that spawned the ethnogenesis of African Americans and other mixed-race people such as the criollas in Mexico, with its unique history of conquest, leading to the development of colorism, a metrics of human worth based on white supremacy and black inferiority.